ENZOOTOGENESIS OF RODENT PLAGUE - O.A. Baitanayev (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the micro-focal structure of the plague infection enzootia. A hypothesis of enzootogenesis based on the “bottleneck” effect in population genetics is proposed. The phenomenon of preservation of the causative agent of the plague in soil amoeba during the inter enzootic period is discussed. The role of fleas in the transmission of a microbe is recognized as local. However, their significance is monopolistic in the epidemiology of the plague in bubonic form.